2017
DOI: 10.3384/cu.2000.1525.1683218
|View full text |Cite
|
Sign up to set email alerts
|

The rainbow flag as friction: transnational imagined communities of belonging among Pakistani LGBTQ activists

Abstract: This article analyzes the frictions the rainbow flag creates between transnational, national and translocal discourses and materialities. It focuses on the ambivalent role that the transnational 'rainbow' space plays for community building for LG-BTQ activists in in Pakistan. The rainbow flag can function as a way to mobilize an imagined transnational community of belonging, enabling people to politicize their experiences of discrimination as a demand of recognition directed at the state. But it can also enabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 17 publications
(4 reference statements)
0
7
0
Order By: Relevance
“…According to these critics, the flag and the Pride parades have become normalised, mainstreamed, and thus harmless. It is used by capitalist market-driven businesses and cities in order to sell their products and services (Klapeer and Laskar 2018;Peterson et al 2018), by nations to wash away the country's image of being homophobic, so-called pinkwashing, and to build an image of the nation as modern and tolerant, so-called homonationalism (Puar 2007;Alm and Martinsson 2016;Laskar et al 2016). It also functions as a tool for attempts by right-wing groups to dismiss immigrants and refugees, accusing them of being backwards and intolerant, often combined with statements about Islam (Brown 2009;Puar 2007).…”
mentioning
confidence: 99%
“…According to these critics, the flag and the Pride parades have become normalised, mainstreamed, and thus harmless. It is used by capitalist market-driven businesses and cities in order to sell their products and services (Klapeer and Laskar 2018;Peterson et al 2018), by nations to wash away the country's image of being homophobic, so-called pinkwashing, and to build an image of the nation as modern and tolerant, so-called homonationalism (Puar 2007;Alm and Martinsson 2016;Laskar et al 2016). It also functions as a tool for attempts by right-wing groups to dismiss immigrants and refugees, accusing them of being backwards and intolerant, often combined with statements about Islam (Brown 2009;Puar 2007).…”
mentioning
confidence: 99%
“…In that sense, we use the term to summarise the different ways people perceive and articulate their 'sameness' (Brubaker and Cooper 2000: 7) within social groups and networks, thus setting clear boundaries towards outsiders. This is a different notion of COB than that of Verdasco (2019) who reserves the term for strong bonds of commonality and mutual support, or Alm and Martinsson's (2016) analysis of the emotional and affective aspects of community building among political activists. Our usage of COB allows us to approach our object of interest in a more general fashion, It encapsulates three questions which can be translated into empirically oriented research.…”
Section: Communities Of Belongingmentioning
confidence: 97%
“…The concept of imagined community can also be useful for understanding sexuality. Indeed, scholars have, in various ways, drawn upon the concept of imagined community when examining LGBTQ + populations (e.g., Alm and Martinsson, 2017; Hollister 1999; Hughes 2008; Jones 2007; King 2008; Ross 2012; Wong and Zhang, 2000; Woolwine 2000). Overall, however, literature on sexualities has largely not focused on gayness as a “community.” Given findings that suggest that collective gay identity may be weakening (e.g., Ghaziani 2014; Seidman 2002), it is worth considering gayness as a community as well.…”
Section: Imagined Community Beyond the Nationmentioning
confidence: 99%
“…Some previous studies that have examined LGBTQ + imagined communities have found that, as with the nation, imagined community can be a source of resilience and strength for those who imagine themselves to be members (e.g., Ross 2012). Others have noted that while the LGBTQ + imagined community can be politically mobilizing, it can also exclude vulnerable members of that supposed community (Alm and Martinsson 2017; Woolwine 2000). Relatedly, research has found that ambivalence about gay communities is common among gay men (Holt 2011).…”
Section: Imagined Community Beyond the Nationmentioning
confidence: 99%